Geodetic observations for the determination of Essential Climate Variables and monitoring hydrological changes - Godah, Walyeldeen
The Global Climate Observing System (GCOS) defines fifty-five Essential Climate Variables (ECVs) as variables that are critical for characterizing the climate system and its changes. The geodetic observations can play an essential role in the determination of these ECVs. The first part of this presentation provides an overview concerning the contribution of geodetic techniques (terrestrial and satellite gravimetry, Global Navigation Satellite Systems (GNSS), satellite altimetry, InSAR, and etc.) for the determination of ECVs. The second part of this presentation focuses on the use of space geodetic data for studying hydrological changes and their correlation with climate indices. As a case study, the area of Sudan (an area characterized by heterogeneous terrestrial hydrological data) is considered. The usefulness of space geodetic data for monitoring hydrological changes over this area is addressed. Moreover, the relation between these hydrological changes and sea surface temperature from both the El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) climate indices is discussed.
Keywords: Seminaria IGiK; GCOS; ECVs; GNSS; InSAR